Formation of Aryl [1-Cyano-4-(dialkylamino)butadienyl] Ketones from Pyridines - Gim, Hyo Jin; Jung, Michael E. (Synthesis, 2019)
Treatment of 2-chloropyridine with LDA and the Weinreb amide of benzoic acid afforded three unusual products, namely N-methylbenzamide, 2-chloropyridine-3-methanol, and the ring-opened addition product. This same final product could also be obtained from 2-chloro-3-benzoylpyridine on treatment with LDA. Mechanistic insight for the formation of these products is provided.
Keywords: pyridines; Weinreb amides; LDA; pyridine ring-openings; anions